Implementing task-based teacher training: Narratives from language classrooms - K. Padmini Shankar, (Journal of Modern Languages, 2021)
This paper aims to document the impact of task-based teacher training on the classroom teaching of two native-speaker English Teaching Assistants (ETAs). The data are drawn from a 30-hour teacher training course offered to the ETAs who taught in two different government schools in Hyderabad, India, as part of the United States India Education Foundation’s Fulbright Fellowship Programme. The training offered to the ETAs consisted of eight modules: teaching vocabulary and grammar, developing listening, speaking, reading and writing and classroom management and lesson planning. Training was offered through tasks, responses to prompts, and case studies. It also included analysis of critical moments that emerged from the everyday teaching of the ETAs. Constructs such as teacher decision-making (Borg, 2006), critical reflection (East, 2014) and pre-service teacher mentoring (Gardiner 2017) have been used to build the theoretical support for the study. A Challenge-Input-Implementation (CII) model is developed to interpret and analyze the data. The data are gathered from three tools: a) reflective journals of ETAs which recorded pertinent issues that emerged from their everyday teaching and possible solutions to these; b) trainer’s field notes that identified critical areas from lesson observation and post-observation conferences; and c) cognitive information sheet which documents ETAs perceptions of how their learning from the training impacted their teaching and what they would like to explore further in their future teaching careers. Findings revealed areas where trainees needed more support (e.g., class control), as well as the strengths that they have developed in instruction delivery (e.g., the ability to make the class interactive).